Optimizing the use of pressurized bladders for the assembly of HL-LHC MQXFB magnets. (1st June 2023) - Ferradas Troitino, J; Ambrosio, G; Bourcey, N; Cheng, D; Devred, A; Felice, H; Ferracin, P; Guinchard, M; Izquierdo Bermudez, S; Kandemir, K; Lusa, N; Milanese, A; et al.
Abstract: The use of pressurized bladders for stress control of superconducting magnets was firstly proposed at Lawrence Berkeley National Laboratory in the early 2000s. Since then, the so-called 'bladders and keys' procedure has become one of the reference techniques for the assembly of high-field accelerator magnets and demonstrators. Exploiting the advantages of this method is today of critical importance for Nb3 Sn-based accelerator magnets, whose production requires the preservation of tight stress targets in the superconducting coils to limit the effects of the strain sensitivity and brittleness of the conductor. The present manuscript reports on the results of an experimental campaign focused on the optimization of the 'bladders and keys' assembly process in the MQXFB quadrupoles. These 7.2 m long magnets shall be among the first Nb3 Sn cryomagnets to be installed in a particle accelerator as a part of the High Luminosity upgrade of the LHC. One of the main practical implications of the bladders technique, especially important when applied to long magnets like MQXFB, is that to insert the loading keys, the opening of a certain clearance in the support structure is required. The procedure used so far for MQXF magnets involved an overstress in the coils during bladder inflation. The work presented here shows that such an overshoot can be eliminated thanks to additional bladders properly positioned in the structure. This optimized method was validated in a short model magnet and in a full-length mechanical model, becoming the new baseline for the series production at CERN Furthermore, the results are supported by numerical predictions using finite element models.